Relationship Building Strategies in Counseling - Thessia Permata Bunda; Mudjiran; Yeni Karneli (Journal Of Psychology, Counseling And Education, 2025)
Relationship in counseling is an important thing, so that the counseling process runs smoothly and effectively and so that clients feel comfortable and accepted in counseling. This writing uses the literature review method by collecting various sources such as books, journals, theses and other relevant websites. In order for the counseling process to run properly and the counseling objectives can be achieved perfectly, it can be seen from how the relationship between the counselor and the client in the counseling process. If the client is YAVIS then the relationship created by the counselor at the beginning of counseling can be said to be successful. Therefore, the relationship in counseling in the main milestone in undergoing the next step or counseling process.